Enhanced electrocatalytic performance of functionalized carbon nanotube electrodes for oxygen reduction in proton exchange membrane fuel cells - Kannan, Ramaiyan; Bipinlal, Unni; Kurungot, Sreekumar; Pillai, Vijayamohanan K. (Physical Chemistry Chemical Physics, 2011)
Although nitrogen doped CNTs (N-CNTs) are considered as a promising alternative to platinized carbon for the oxygen reduction reaction (ORR) in polymer electrolyte membrane fuel cells (PEMFCs), the origin of the enhanced ORR activity with N-CNTs is not clear at present. Among several plausible reasons, the exposure of edge plane and creation of impurity band/surface states near the Fermi level are considered as major causes behind the catalytic activity. However, CNTs without nitrogen doping are not known to catalyze the ORR. In this work, we study the ORR activity of functionalized carbon nanotubes with different functional groups, such as sulfonic acid and phosphonic acid, in order to understand the role of surface functionalities in catalyzing the reaction. Functionalized CNTs show significantly enhanced activity towards the ORR, while CNTs without such surface functional groups do not reveal any such special ORR activity. Linear sweep voltammetry experiments with different rotation rates show diffusion controlled limiting current values for functionalized CNTs, and the `n' values derived from Koutecky-Levich plots are 3.3 and 1.7 for S-MWCNTs and P-MWCNTs, respectively. This work demonstrates the ORR activity of functionalized MWCNTs, which opens up new strategies for electrocatalyst design in PEMFCs.

Ex-situ dispersion of core-shell nanoparticles of Cu-Pt on an in situ modified carbon surface and their enhanced electrocatalytic activities - Dhavale, Vishal M.; Unni, SreeKuttan M.; Kagalwala, Husain N.; Pillai, Vijayamohanan K.; Kurungot, Sreekumar (Chemical Communications, 2011)
Direct dispersion of core-shell nanoparticles on a carbon support (Cu@ Pt/C) has been achieved while retaining the essential core-shell features of the nanoparticles by adopting an in situ surface modification-cum-anchoring strategy.

Efficient oxygen reduction electrocatalyst from graphene by simultaneously generating pores and nitrogen doped active sites - Palaniselvam, Thangavelu; Aiyappa, Harshitha Barike; Kurungot, Sreekumar (Journal of Materials Chemistry, 2012)
A simple way to simultaneously create pores and nitrogen doped active sites on graphene for the electrochemical oxygen reduction reaction (ORR) is developed. The key aspect of the process is the in-situ generation of Fe2O3 nanoparticles and their concomitant dispersion on graphene by pyrolyzing graphene oxide (GO) with the iron phenanthroline complex. Thus the deposited Fe2O3 nanoparticles act as the seeds for pore generation by etching the carbon layer along the graphene-Fe2O3 interface. Detection of the presence of Fe3C along with Fe2O3 confirms carbon spill-over from graphene as a plausible step involved in the pore engraving process. Since the process offers a good control on the size and dispersion of the Fe2O3 nanoparticles, the pore size and distribution also could be managed very effectively in this process. As the phenanthroline complex decomposes and gives Fe2O3 nanoparticles and subsequently the pores on graphene, the unsaturated carbons along the pore openings simultaneously capture nitrogen of the phenanthroline complex and provide very efficient active sites for ORR under alkaline conditions. The degree of nitrogen doping and hence the ORR activity could be further improved by subjecting the porous material for a second round of nitrogen doping using iron-free phenanthroline. This porous graphene enriched with the N-doped active sites effectively reduces oxygen molecule through a 3e(-) pathway, suggesting a preferential shift towards the more favourable 4e(-) route compared to the 2e(-) reaction as reported for many N-doped carbon nano-morphologies. The 90 mV onset potential difference for oxygen reduction as compared to the state-of-the art 20 wt% Pt/C catalyst is significantly low compared to the overpotentials in the range of 120-200 mV reported in the literature for few N-doped graphenes.

Effect of the viscosity of poly(benzimidazole) on the performance of a multifunctional electrocatalyst with an ideal interfacial structure - Balan, Beena K.; Unni, Bipinlal; Chaudhari, Harshal D.; Kharul, Ulhas K.; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2013)
A novel electrocatalyst system with unique multifunctional characteristics, originated by the presence of a proton conducting polybenzimidazole (PBI-BuI) bound layer and electron conducting hollow carbon nanofibers (CNF) with catalytically active Pt nanoparticles, has been devised based on a simple strategy. This was achieved by decorating Pt nanoparticles along the inner cavity, as well as on the outer walls of the hollow CNF support (F-Pt). In a further extension, a low molecular weight PBI, synthesized by optimizing the experimental parameters, was incorporated into the inner cavity and along the outer surfaces of F-Pt. Excellent dispersion of the Pt nanoparticles was achieved by properly utilizing the available carbon surface results in improved electrocatalytic activity, while the CNF backbone ensures high electron conductivity as well. The polymer binder coverage formed along the inner and outer wall surfaces provides an efficient triple phase boundary (TPB) around the Pt nanoparticles to facilitate the electrode reactions. The amount and the viscosity of the PBI-BuI in the electrode material were systematically varied to study the influence on the electrochemical performance. Transmission electron microscopy analysis confirms PBI insertion into the tubular cavity of CNF. Pore size distribution analysis implies that both the viscosity and the amount of PBI-BuI have a pivotal role in defining the microstructure of the electrode. Electrochemical studies using cyclic voltammetry (CV) and rotating disc electrode (RDE) reveal the exceptionally high activity of this hybrid material with an improved electrochemically active area. The significant improvement for the oxygen reduction reaction is further confirmed by the single cell analysis also. The high power density displayed by the PBI-BuI based system, as compared to the Nafion based system, validates the conceptualization of the well controlled triple-phase boundary in the system. These results demonstrate that PBI-BuI has a constructive effect in tuning the electrochemical activity at an optimum amount and at a favourable viscosity of the proton conducting polymer.

Electrochemically grown nanoporous MnO2 nanowalls on a porous carbon substrate with enhanced capacitance through faster ionic and electrical mobility - Anothumakkool, Bihag; Kurungot, Sreekumar (Chemical Communications, 2014)
We report the deposition of uniform porous MnO2 nanowalls on a conducting carbon fiber substrate using a simple electrochemical method, which produces ordered nano-channels demarcated by the MnO2 walls for easy ion transport and a continuous electron path created by the carbon backbone. The system achieves a specific capacitance of 1149 F g(-1) and retains 565 F g(-1) even at dragging conditions as high as 100 A g(-1).

Electrodeposited polyethylenedioxythiophene with infiltrated gel electrolyte interface: a close contest of an all-solid-state supercapacitor with its liquid-state counterpart - Anothumakkool, Bihag; Torris, Arun A. T.; Bhange, Siddheshwar N.; Badiger, Manohar V.; Kurungot, Sreekumar (Nanoscale, 2014)
We report the design of an all-solid-state supercapacitor, which has charge storage characteristics closely matching that of its liquid-state counterpart even under extreme temperature and humidity conditions. The prototype is made by electro-depositing polyethylenedioxythiophene (PEDOT) onto the individual carbon fibers of a porous carbon substrate followed by intercalating the matrix with polyvinyl alcohol-sulphuric acid (PVA-H2SO4) gel electrolyte. The electrodeposited layer of PEDOT maintained a flower-like growth pattern along the threads of each carbon fiber. This morphology and the alignment of PEDOT led to an enhanced surface area and electrical conductivity, and the pores in the system enabled effective intercalation of the polymer-gel electrolyte. Thus, the established electrode-electrolyte interface nearly mimics that of its counterpart based on the liquid electrolyte. Consequently, the solid device attained very low internal resistance (1.1 Omega cm(-2)) and a high specific capacitance (181 F g(-1)) for PEDOT at a discharge current density of 0.5 A g(-1). Even with a high areal capacitance of 836 mF cm(-2) and volumetric capacitance of 28 F cm(-3), the solid device retained a mass-specific capacitance of 111 F g(-1) for PEDOT. This is in close agreement with the value displayed by the corresponding liquid-state system (112 F g(-1)), which was fabricated by replacing the gel electrolyte with 0.5 M H2SO4. The device also showed excellent charge-discharge stability for 12 000 cycles at 5 A g(-1). The performance of the device was consistent even under wide-ranging humidity (30-80%) and temperature (-10 to 80 degrees C) conditions. Finally, a device fabricated by increasing the electrode area four times was used to light an LED, which validated the scalability of the process.

Enhanced catalytic activity of polyethylenedioxythiophene towards tri-iodide reduction in DSSCs via 1-dimensional alignment using hollow carbon nanofibers - Anothumakkool, Bihag; Game, Onkar S.; Bhange, Siddheshwar N.; Kumari, Tanya; Ogale, Satishchandra B.; Kurungot, Sreekumar (Nanoscale, 2014)
Here, we report a highly conducting 1-dimensionally (1-D) aligned polyethylenedioxythiophene (PEDOT) along the inner and outer surfaces of a hollow carbon nanofiber (CNF) and its application as a counter electrode in a dye sensitized solar cell (DSSC). The hybrid material (CP-25) displays a conversion efficiency of 7.16% compared to 7.30% for the standard Pt counter electrode, 4.48% for bulk PEDOT and 5.56% for CNF. The enhanced conversion efficiency of CP-25 is attributed to the accomplishment of high conductivity and surface area of PEDOT through the 1-D alignment compared to its bulk counterpart. Reduced charge transfer resistance and high conductivity of CP-25 could be proven by cyclic voltammetry, impedance analysis and Tafel experiments. Further, through a long-term stability test involving efficiency profiling for 20 days, it is observed that CP-25 possesses excellent durability compared to the bulk PEDOT.

Effect of b site coordination environment in the ORR activity in disordered brownmillerites Ba2In2-xCexO5+delta - Jijil, Chamundi P.; Bhange, Siddheshwar N.; Kurungot, Sreekumar; Devi, R. Nandini (ACS Applied Materials & Interfaces, 2015)
Ba2In2O5 brownmillerites in which the In site is progressively doped with Ce exhibit excellent oxygen reduction activity under alkaline conditions. Ce doping leads to structural changes advantageous for the reaction. Twenty-five percent doping retains the ordered structure of brownmillerite with alternate layers of tetrahedra and octahedra, whereas further increase in Ce concentration creates disorder. Structures with disordered oxygen atoms/vacancies are found to be better oxygen reduction reaction catalysts probably aided by isotropic ionic conduction, and Ba2In0.5Ce1.5O5+delta is the most active. This enhanced activity is correlated to the more symmetric Ce site coordination environment in this compound. Stoichiometric perovskite BaCeO3 with the highest concentration of Ce shows very poor activity emphasizing the importance of oxygen vacancies, which facilitate O-2 adsorption, in tandem with catalytic sites in oxygen reduction reactions.
Keywords: brownmillerite; fuel cell; oxygen disorder; oxygen reduction reaction; Rietveld refinement

Electrochemical preparation of nitrogen-doped graphene quantum dots and their size-dependent electrocatalytic activity for oxygen reduction - Shinde, Dhanraj B.; Dhavale, Vishal M.; Kurungot, Sreekumar; Pillai, Vijayamohanan K. (Bulletin of Materials Science, 2015)
Here we report a remarkable transformation of nitrogen-doped multiwalled carbon nanotubes (MWCNTs) to size selective nitrogen-doped graphene quantum dots (N-GQDs) by a two-step electrochemical method. The sizes of the N-GQDs strongly depend on the applied anodic potential, moreover increasing potential resulted in a smaller size of N-GQDs. These N-GQDs display many unusual size-dependant optoelectronic (blue emission) and electrocatalytic (oxygen reduction) properties. The presence of N dopants in the carbon framework not only causes faster unzipping of MWCNTs but also provides more low activation energy site for enhancing the electrocatalytic activity for technologically daunting reactions like oxygen reduction. The smaller size of N-GQDs has shown better performance as compared to the large N-GQDs. Interestingly, N-GQDs-3 (size = 2.5 +/- 0.3 nm, onset potential = 0.75 V) show a 30-mV higher positive onset potential shift compared to that of N-GQDs-2 (size = 4.7 +/- 0.3 nm, onset potential = 0.72 V) and 70 mV than that of N-GQDs-1 (size = 7.2 +/- 0.3, onset potential = 0.68 V) for oxygen reduction reaction (ORR) in a liquid phase. These result in the size-dependent electrocatalytic activity of N-GQDs for ORR as illustrated by the smaller sized N-GQDs (2.5 +/- 0.3 nm) undoubtedly promising metal-free electrocatalysts for fuel cell applications.
Keywords: fuel cells; MWCNTs; N-GQDs; oxygen reduction reaction; unzipping

Enhanced proton conduction by post-synthetic covalent modification in a porous covalent framework - Samanta, Partha; Desai, Aamod V.; Anothumakkool, Bihag; Shirolkar, Mandar M.; Karmakar, Avishek; Kurungot, Sreekumar; Ghosh, Sujit K. (Journal of Materials Chemistry A, 2017)
A highly chemically stable porous covalent framework (PCF-1) based on ether linkages has been synthesized, which exhibits no loss up to similar to 500 degrees C along with retention of integrity under acidic, basic and oxidative reagent conditions. Owing to its thermal and chemical stability, post-synthetic covalent modification was executed for the introduction of pendant sulphonic acid (-SO3H) groups. The covalently modified compound (PCF-1-SO3H) presents a remarkably high conductivity (ca. 0.026 S cm(-1)), with an similar to 130 fold enhancement in proton conductivity over the parent compound. This value is comparable with those of commercially used Nafion-based proton conducting materials and stands as the highest known value in the regime of post-synthetically modified porous organic frameworks. It is noteworthy to mention that PCF-1 is stable in both acidic and alkaline media, which is not commonly observed for most of the porous materials trialed as proton conducting materials, including metal organic frameworks.

Efficient electrochemical oxygen reduction to hydrogen peroxide by transition metal-doped silicate Sr0.7Na0.3SiO3-delta - Thundiyil, Shibin; Kurungot, Sreekumar; Devi, R. Nandini (ACS Applied Materials & Interfaces, 2021)
Electrochemical oxygen reduction in a selective two-electron pathway is an efficient method for onsite production of H2O2. State of the art noble metal-based catalysts will be prohibitive for widespread applications, and hence earth-abundant oxide-based systems are most desired. Here we report transition metal (Mn, Fe, Ni, Cu)-doped silicates, Sr0.7Na0.3SiO3-delta, as potential electrocatalysts for oxygen reduction to H2O2 in alkaline conditions. These novel compounds are isostructural with the parent Sr0.7Na0.3SiO3-delta and crystallize in monoclinic structure with corner-shared SiO4 groups forming cyclic trimers. The presence of Na stabilizes O vacancies created on doping, and the transition metal ions provide catalytically active sites. Electrochemical parameters estimated from Tafel and Koutechy-Levich plots suggest a two-electron transfer mechanism, indicating peroxide formation. This is confirmed by the rotating ring disc electrode method, and peroxide selectivity and Faradaic efficiency are calculated to be in the range of 65-82% and 50-68%, respectively, in a potential window 0.3 to 0.6 V (vs RHE). Of all the dopants, Ni imparts the maximum selectivity and efficiency as well as highest rate of formation of H2O2 at 1.65 mu mol s(-1).
Keywords: H2O2; mixed metal oxide; ORR; silicate

Enhanced electrocatalytic activity of PtRu/nitrogen and sulphur co-doped crumbled graphene in acid and alkaline media - Pang, Liuqing; Miao, Yuanyuan; Bhange, Siddheshwar N.; Barras, Alexandre; Addad, Ahmed; Roussel, Pascal; Amin, Mohammed A.; Kurungot, Sreekumar; Szunerits, Sabine; Boukherroub, Rabah (Journal of Colloid and Interface Science, 2021)
The low mass activity and high price of pure platinum (Pt)-based catalysts predominantly limit their large-scale utilization in electrocatalysis. Therefore, the reduction of Pt amount while preserving the electrocatalytic efficiency represents a viable alternative. In this work, we prepared new PtRu2 nanoparticles supported on sulphur and nitrogen co-doped crumbled graphene with trace amounts of iron (PtRu2/PF) electrocatalysts. The PtRu2/PF catalysts exhibited enhanced electrocatalytic performance and stability for the hydrogen evolution reaction (HER) at pH = 0. Moreover, the prepared PtRu2/PF electrocatalyst displayed higher HER activity than commercial 20% Pt/C. The PtRu2/PF catalyst achieved a current density of 10 mA cm(-2) at an overpotential value of only 22 mV for HER, performing better activity than many other Pt-based electrocatalysts. Besides, the PtRu2/PF revealed a good performance for the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) in alkaline media. The PtRu2/PF catalyst recorded a current density of 10 mA cm(-2) at an overpotential of only 270 mV for OER in KOH (1.0 M) solution and an onset potential of 0.96 V vs. RHE (at 1 mA cm(-2)) for ORR in KOH (0.1 M) solution. (C) 2021 Elsevier Inc. All rights reserved.
Keywords: HER; OER; ORR; PtRu2; Sulphur and nitrogen co-doped crumbled graphene

Electrodeposited layered sodium vanadyl phosphate (NaxVOPO4 center dot nH(2)O) as cathode material for aqueous rechargeable zinc metal batteries - Dilwale, Swati; Ghosh, Meena; Vijayakumar, Vidyanand; Kurungot, Sreekumar (Energy & Fuels, 2022)
Aqueous rechargeable zinc metal batteries (ARZMBs) present a safer and cost-effective solution for energy storage in stationary applications. However, a major challenge is the lack of suitable cathode materials simultaneously exhibiting high operating voltage and long cycling stability. Herein, we report the polyanionic sodium-intercalated layered vanadyl phosphate [NaxVOPO4 center dot nH(2)O (NVP)] as a suitable high-voltage and stable cathode for ARZMBs. This work employs a simpler electrochemical route (electrodeposition) for the synthesis of NVP over functionalized carbon fiber substrates and its application as a binder-free cathode in ARZMBs. The electrodeposited NVP possesses a morphology of vertically aligned well-separated nanosheet bundles resembling a flower. When used as the ARZMB cathode, the NVP electrode delivers a specific discharge capacity of 100 mA h g(-1) at 0.033 A g(-1) and high cycling stability (98% retention of the initial capacity over 1100 cycles at 0.333 A g(-1)) in a mild aqueous electrolyte with moderate zinc salt concentration. The observed electrochemical performance of NVP is credited to the synergistic effect of unique nanoflower morphology, the pillaring effect offered by the intercalated Na, and the intimate contact of the active material with the carbon fiber network. These factors are favorable for enhancing the transport of the electrolyte ions and electrons and maintaining the structural stability of the electrode during long-term cycling. The NVP electrode could also deliver appreciable performance (a discharge capacity of 73 mA h g(-) 1 and a current density of 0.033 A g(-1)) in quasi-solidstate ARZMB cells employing PVA/Zn(CF3SO3)(2) gel electrolyte.

Enhanced proton conductivity in amino acid based self-assembled non-porous hydrogen-bonded organic frameworks - Pramanik, Titas; Anand, Ashish; Pandikassala, Ajmal; Illathvalappil, Rajith; Kurungot, Sreekumar; Row, T. N. Guru (Chemical Communications, 2022)
beta-Alaninium oxalate hemihydrate, glycinium oxalate, and L-leucinium oxalate salt-cocrystals as non-porous self-assembled hydrogen-bonded organic frameworks afforded proton conductivity of 2.43 x 10(-2) S cm(-1) (60 degrees C, 95% RH), 3.03 x 10(-2) S cm(-1) (60 degrees C, 95% RH), and 1.19 x 10(-2) S cm(-1) (80 degrees C, 95% RH), respectively. These materials possess an extensive 3-dimensional network of hydrogen bonds in their crystal structures, making them efficient proton conducting membranes. The reduction in conductivity values over 10(-1) S cm(-1) order upon exposure of the samples to a D2O atmosphere in extreme conditions ratified the role of humidity for the conduction of protons. This work explores the relationship between structural features and proton conductivity for the design of proton conducting membranes that are easy to synthesize, eco-friendly, and cheap with potential for futuristic applications.

Electrode|electrolyte interface enhancement in quasi-solid-state zinc-air batteries through an anion conducting polymer electrolyte interlayer by in situ polymerization - Kurian, Maria; Vijayakumar, Vidyanand; Manna, Narugopal; Kanheerampockil, Fayis; Bhat, Suresh; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2023)
This work introduces a novel concept of electrode|electrolyte interface enhancement using an ultraviolet (UV) light-assisted in situ polymerization strategy to improve the performance of quasi-solid-state zinc-air batteries (ZABs). The suitability of the UV polymerization strategy to process a mechanically stable OH- conducting anion exchange polymer electrolyte membrane (AEPEM) reinforced by a glass fiber (GF) separator is also reported. The in situ polymerized ionomer-skin/interlayer (a thin anion-conducting polymer coating over the air-cathode of ZAB) acts as a buffer layer to narrow down the performance gap generally observed between ZABs possessing quasi-solid-state electrolytes and standard liquid electrolytes, respectively. For instance, when combined with the in situ polymerization strategy, a rechargeable ZAB (rZAB) based on an AEPEM-GF composite membrane delivered a high power density of 140 mW cm(-2), higher than that of the one without an in situ polymerized ionomer interlayer (120 mW cm(-2)). Notably, in a flexible rZAB configuration, this new strategy resulted in enhanced rate capability and cycling stability for 14 h at an operating current density of 2 mA cm(-2).